Urban Tourism Destination Development: Its Contribution to the Tourism Economy and Hospitality Industry in Malang City - Ni Wayan Gita Sadhana Savitri; Ni Kadek Sri Mirayani; I Gusti Ngurah Oka Widjaya; Ni Putu Ariningsih; Made Sera Septiani (Tourism and Hospitality Insights, 2026)
Introduction: The development of urban tourism has become an important strategy to enhance destination competitiveness and strengthen the contribution of tourism to regional economic growth. Malang City, as one of the tourism destinations in East Java, has urban tourism characteristics that are supported by historical heritage, cultural resources, culinary attractions, educational activities, creative economy, and hospitality services. This study aims to analyze the development of urban tourism destinations in Malang City and examine their contribution to tourism economic development and the hospitality industry. Methods: This research employed a qualitative approach using observation and literature review as data collection techniques. The collected data were analyzed through qualitative data analysis procedures, including data reduction, data presentation, and interpretation to identify patterns related to urban tourism development. Results: The findings indicate that Malang City has significant potential as an urban tourism destination through its diverse cultural heritage, historical attractions, creative community-based tourism, culinary experiences, and urban activities. Accessibility, amenities, and accommodation facilities also support tourism development through adequate infrastructure, public facilities, and the growth of the hospitality sector. Furthermore, tourism institutions and the positive image of Malang City as an educational and cultural city contribute to strengthening destination competitiveness. The development of urban tourism in Malang City generates economic benefits through increased tourist expenditure, business opportunities, employment creation, and the strengthening of the hospitality sector, particularly the hotel industry. Conclusion: The findings indicate that Malang City possesses strong potential as an urban tourism destination by leveraging its historical heritage, cultural assets, culinary attractions, community creativity, and well-developed urban facilities. The integration of the 6A tourism components; attractions, activities, accessibility, amenities, accommodation, and ancillary services, enhances destination competitiveness, supports visitor satisfaction, and strengthens the tourism economy and hospitality industry. These findings suggest that integrated urban tourism development is a strategic approach to promoting sustainable tourism growth and regional economic development in Malang City.